1998
DOI: 10.1046/j.1365-313x.1998.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of components of the oxidative cross‐linking of glycoproteins and of callose synthesis in papillae formed during the interaction between non‐pathogenic strains ofXanthomonas campestris andFrench bean mesophyll cells

Abstract: SummaryImmunogold labelling was used to probe the responses of mesophyll cells in French bean (Phaseolus vulgaris L.) to an hrpA mutant of Xanthomonas campestris pv. vesicatoria and a saprophytic strain of X.c. The non-pathogenic strains both caused localized alterations to the plant cell wall and formation of large papillae in adjacent cells. Immunocytochemistry showed the co-localization, in the cell wall and paramural deposits, of an M r 42 000 proline-rich glycoprotein with chitin-binding activity (CBPRP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
97
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(100 citation statements)
references
References 38 publications
0
97
1
1
Order By: Relevance
“…Pectinacetylesterases and pectinmethylesterases control the degree of acetyl and methyl esterification of cell wall polygalacturonans, and PGIPs inhibit cell expansion by inhibiting the cell wall-loosening activity of polygalacturonases that hydrolyze pectin. Although significant changes in the cross-linking of Hyp-rich glycoproteins following elicitor treatment have not been observed (Brisson et al, 1994;Wojtaszek et al, 1995;Brown et al, 1998), it is possible that the knockdown of basal levels of PRX33 and PRX34 leads to cell expansion by diminishing peroxidase-catalyzed crosslinking of cell wall polymers, which in turn affects the regulation of genes involved in cell expansion. A similar compensatory mechanism has also been observed in mutants lacking the cellulose synthase gene CESA3, where a reduction of cellulose content affected the pectin and xyloglucan composition of the cell wall (Cañ o-Delgado et al, 2003;Bosca et al, 2006).…”
Section: Proteomic Changes In the Transgenic Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pectinacetylesterases and pectinmethylesterases control the degree of acetyl and methyl esterification of cell wall polygalacturonans, and PGIPs inhibit cell expansion by inhibiting the cell wall-loosening activity of polygalacturonases that hydrolyze pectin. Although significant changes in the cross-linking of Hyp-rich glycoproteins following elicitor treatment have not been observed (Brisson et al, 1994;Wojtaszek et al, 1995;Brown et al, 1998), it is possible that the knockdown of basal levels of PRX33 and PRX34 leads to cell expansion by diminishing peroxidase-catalyzed crosslinking of cell wall polymers, which in turn affects the regulation of genes involved in cell expansion. A similar compensatory mechanism has also been observed in mutants lacking the cellulose synthase gene CESA3, where a reduction of cellulose content affected the pectin and xyloglucan composition of the cell wall (Cañ o-Delgado et al, 2003;Bosca et al, 2006).…”
Section: Proteomic Changes In the Transgenic Cell Linesmentioning
confidence: 99%
“…In addition, succinate, malate, and fumarate are part of the citric acid cycle in mitochondria and the glyoxylic acid cycle in peroxisomes. Thus, another possibility for the changes in the accumulation of these metabolites following elicitation is that they are a consequence of exocytosis events that are known to occur in plant cell-pathogen interactions (Brown et al, 1998) and may involve peroxisomes that move toward and accumulate at the site of infection (Scheel, 1998;Lipka et al, 2005;An et al, 2006;Hardham et al, 2008).…”
Section: Metabolic Changes In the Transgenic Cell Linesmentioning
confidence: 99%
“…Most of the earlier studies on infection-induced accumulation of HRGPs were carried out in dicotyledons, e.g. French bean infected with Colletotrichum lindemuthianum (Templeton et al 1990;Millar et al 1992;Bindschedler et al 2006), lettuce infected with Pseudomonas syringae (Bestwick et al 1995), French bean infected with Xanthomonas campestris (Brown et al 1998) and tobacco leaves infected by Erysiphe cichoracearum (Raggi 2000). In recent years, reports have emerged on the accumulation of HRGPs in monocotyledons as a response to pathogens, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This polymer was thought to contribute to a physical barrier that slowed the invading microorganism and enabled the plant to focus anti-microbial compounds, such as wall-degrading enzymes, phytoalexins and active oxygen species, upon them [10]. Recently, it has been shown that a single glucan synthase-like isoform in Arabidopsis, GLUCAN SYNTHASE-LIKE5 (GSL5)/ POWDERY MILDEW RESISTANCE4 (PMR4), is essential to synthesise papillary callose [11 ,12 ].…”
Section: Introductionmentioning
confidence: 99%